1995
DOI: 10.1007/bf01103459
|View full text |Cite
|
Sign up to set email alerts
|

Studies on fungi associated with tomato fruits and effectiveness of some commercial fungicides against three pathogens

Abstract: Among 39 fungal species and one variety belonging to 16 genera isolated from 116 healthy tomato fruits collected from markets in Assiut, Egypt, during 1994, Aspergillus niger was found to be the most prevalent, being isolated from 84.6% of the samples. Of 11 species recovered from 156 diseased tomatoes, Alternaria alternata, Rhizopus stolonifer and A. niger were the most common and isolated from 52.7%, 35.9% and 25.0% of the samples, respectively. Experiments for comparison of the effects of medium containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
4
8
0
Order By: Relevance
“…Our results of postharvest pathogens isolated from tomato fruits are consistent with the previously reported studies (Abdel-Mallek et al 1995;Wade et al 2003;Fajola 2006), whereas, most of fungal isolated pathogens were around the same fungi of these investigations. In our investigation, the results of the pathogenicity tests showed that Rhizopus sp.…”
Section: Discussionsupporting
confidence: 93%
“…Our results of postharvest pathogens isolated from tomato fruits are consistent with the previously reported studies (Abdel-Mallek et al 1995;Wade et al 2003;Fajola 2006), whereas, most of fungal isolated pathogens were around the same fungi of these investigations. In our investigation, the results of the pathogenicity tests showed that Rhizopus sp.…”
Section: Discussionsupporting
confidence: 93%
“…In this respect, the use of Na-hypochlorite has been proved to be effective for the control of passion fruit rot-development caused by fungal species most commonly encountered from passion fruits (Ismail, 2001). Also, Na-hypochlorite is reported to be lethal to fungal propagules and fungi in vitro (Mehrotra, 1998) and to have good curative properties against tomato fruit rots especially those caused by Alternaria alternata and Aspergillus niger (Abdel-Mallek et al, 1995). Control of brown spots of passion fruits (caused by A. alternata and A. passiflorae ) is by pruning and destroying the debris and by spraying the passion trees (vines) regularly with fungicide (Snowdon, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…The technique used for enumeration and isolation of mycobiota was adopted from Abdel-Mallek et al (1995). Individual samples were put in clean polyethylene bags and aliquots of 100 ml of sterilized tap water were added.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the identified fungi, R. stolonifer was considered as the one to cause fast and extensive rotting of a wide range of vegetable and fruit hosts (Adikaram, 1993). In markets in Asiut, Egypt, Abdel-Mallek et al (1995) and Ziedan and Farrag (2008) reported that R. stolonifer from diseased tomatoes and peaches was isolated at a frequency of 35.9% and 56.5%, respectively. This last value is only exceeded by Aspergillus niger and A. alternata.…”
mentioning
confidence: 97%